2001
DOI: 10.1021/ja003607o
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Transfer Reactions between Nitroalkanes and Hydroxide Ion under Non-Steady-State Conditions. Apparent and Real Kinetic Isotope Effects

Abstract: The kinetics of the proton-transfer reactions between 1-nitro-1-(4-nitrophenyl)ethane (NNPE(H(D))) and hydroxide ion in water/acetonitrile (50/50 vol %) were studied at temperatures ranging from 289 to 319 K. The equilibrium constants for the reactions are large under these conditions, ensuring that the back reaction is not significant. The extent of reaction/time profiles during the first half-lives are compared with theoretical data for the simple single-step mechanism and a 2-step mechanism involving initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Hydrogen’s small mass and de Broglie uncertainty in position near the transition state (TS) contributes to the tunneling effect . Observations of inflated primary kinetic isotope effects (1° KIEs) and temperature under- or overdependence of 1° KIEs versus values predicted by semi-classical transition state (TS) theory are often used to suggest H-tunneling. Although relatively less used in the general chemistry field, abnormal secondary (2°) KIEs can also function as an indicator for H-tunneling. These abnormalities include inflated 2° KIEs with respect to the values predicted by the semi-classical TS theory and larger 2° KIEs for H-transfer than for D-transfer, i.e., a 1° isotope effect on 2° KIEs. ,− Often, the inflated 2° KIEs were explained in terms of 1° H-tunneling and 1°/2° H coupled motions, in which part of the 2° H out of plane bending vibrational mode is converted to a translational mode, leading to an increase in 2° KIE. , Within this explanation, since H-tunneling is more significant than D-tunneling, the effects of 1°/2° H coupled motions are more significant for the former than the latter, leading to a larger 2° KIE in the former process. However, even if there is other evidence demonstrating H-tunneling, some solution and enzymatic H-transfers still show no 1° isotope effect on 2° KIEs. , Furthermore, we recently reported a deflated 2° KIE and no 1° isotope effect on 2° KIEs for a solution hydride transfer reaction that cannot be explained by the traditional theories .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen’s small mass and de Broglie uncertainty in position near the transition state (TS) contributes to the tunneling effect . Observations of inflated primary kinetic isotope effects (1° KIEs) and temperature under- or overdependence of 1° KIEs versus values predicted by semi-classical transition state (TS) theory are often used to suggest H-tunneling. Although relatively less used in the general chemistry field, abnormal secondary (2°) KIEs can also function as an indicator for H-tunneling. These abnormalities include inflated 2° KIEs with respect to the values predicted by the semi-classical TS theory and larger 2° KIEs for H-transfer than for D-transfer, i.e., a 1° isotope effect on 2° KIEs. ,− Often, the inflated 2° KIEs were explained in terms of 1° H-tunneling and 1°/2° H coupled motions, in which part of the 2° H out of plane bending vibrational mode is converted to a translational mode, leading to an increase in 2° KIE. , Within this explanation, since H-tunneling is more significant than D-tunneling, the effects of 1°/2° H coupled motions are more significant for the former than the latter, leading to a larger 2° KIE in the former process. However, even if there is other evidence demonstrating H-tunneling, some solution and enzymatic H-transfers still show no 1° isotope effect on 2° KIEs. , Furthermore, we recently reported a deflated 2° KIE and no 1° isotope effect on 2° KIEs for a solution hydride transfer reaction that cannot be explained by the traditional theories .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that several organic reactions, previously believed to follow simple second-order kinetics, pass through kinetically significant intermediates and that the reactions do not achieve the steady-state before late in the first half-life. These include the proton-transfer reactions between methylarene radical cations and pyridines, , the proton-transfer reaction between a nitroalkane and hydroxide ion, a hydride-transfer reaction between NAD + and NADH model compounds, the S N 2 reaction between methyl iodide and p -nitrophenoxide ion, and the classical E2 elimination reaction between 2-( p -nitrophenyl)ethyl bromide and alkoxide ions …”
Section: Introductionmentioning
confidence: 99%
“…A factor of importance in the study of proton transfer reactions is the position of equilibrium. We have recently pointed out that in order to avoid the complications accompanying D/H exchange, proton transfer reactions must lie far to the right . The p K a of MPA +• in acetonitrile has been estimated to be equal to 3 from the value determined in dimethyl sulfoxide while that for 2,6-LUT in acetonitrile has been reported to be 15.4.…”
Section: Resultsmentioning
confidence: 99%
“…We have pointed out that there may be a number of different combinations of rate constants ( k f , k b , and k p ) which give acceptable fits for any one extent of reaction−time profile. , Extensive analysis of theoretical data for the two-step mechanism has shown that unique fit of experimental to theoretical data can be achieved by concurrent fitting of data for both ArCH 3 +• and ArCD 3 +• . This involves the assumption that only the rate constants for proton and deuteron transfer steps ( k p H and k p D ) are affected by the isotopic change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation